Proceedings of the 2nd International Conference on Compute and Data Analysis 2018
DOI: 10.1145/3193077.3193078
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Categorising Profane Words in Hate Speech

Abstract: This study attempts to explore the different types of Hate Speech appearing in social media by identifying profane words used in hate speech. This study also compares the profane words used in different generations to assist in identifying the user's profile. Fivehundred (500) comments posted on YouTube on the abusive topics were collected. Profane words are classified into eight different types of hate speech. The finding shows 35% of profane words found in our sample are words related to sexual orientation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
0
18
0
2
Order By: Relevance
“…Lexical dictionaries and their limitations in feelings evaluation were addressed in [14,55,56]. In Teodorescu et al [55], each slang expression is manually annotated with meanings assigned to it.…”
Section: Lexicon Dictionary and Ontology-based Solutionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lexical dictionaries and their limitations in feelings evaluation were addressed in [14,55,56]. In Teodorescu et al [55], each slang expression is manually annotated with meanings assigned to it.…”
Section: Lexicon Dictionary and Ontology-based Solutionsmentioning
confidence: 99%
“…According to Teh et al [14], the use of a lexical dictionary is not sufficient to detect the presence of hate speech in texts written in natural language. The authors indicated that the evolution of vocabulary must be considered for this purpose [14]. Teh et al [14] organized hate terms into eight categories.…”
Section: Lexicon Dictionary and Ontology-based Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Segundo Waseem, Thorne, & Bingel (2018), os trabalhos de análise de sentimentos não consideram adequadamente a influência de questões sociais, geográficas e culturais; tal fator prejudica sua eficácia. Segundo Teh et al (2018), a utilização de um dicionário léxico não é suficiente para detectar a presença de discurso de ódio em textos escritos em linguagem natural, uma vez que a evolução do vocabulário deve ser considerada. O estudo propõe a categorização dos termos de ódio em 8 categorias distintas.…”
Section: Soluções Baseadas Em Dicionário Léxico E Em Ontologiasunclassified